A study to assess hepatic steatosis and fibrosis in chronic hepatitis B patients with the help of non-invasive tests - Gaurav Singh; Kuldeep Chandel; Mandavi Agarwal; Aniket Ashok Satale; Neha Rathore (Asian Journal of Medical Sciences, 2025)
Background: Chronic hepatitis B (CHB) is a persistent global health issue, frequently leading to hepatic fibrosis and steatosis. Although liver biopsy remains the diagnostic benchmark, its invasiveness necessitates safer alternatives. Non-invasive methods such as FibroScan, aspartate transaminase to platelet ratio index (APRI), and Fibrosis-4 (FIB-4) scores have shown promise in assessing liver pathology. Aims and Objectives: To evaluate the diagnostic performance of APRI, FIB-4, and FibroScan in detecting hepatic fibrosis and steatosis in CHB patients and their correlation with biochemical and virological parameters. Materials and Methods: This cross-sectional study was conducted at Maharani Laxmi Bai Medical College, Jhansi, from January 2023 to June 2024. A total of 112 patients with CHB were enrolled. Liver stiffness and steatosis were assessed using FibroScan and controlled attenuation parameters. APRI and FIB-4 scores were calculated, and laboratory values, including aspartate aminotransferase (AST), alanine aminotransferase (ALT), and hepatitis B virus (HBV) DNA, were analyzed. Results: Advanced FIB-4 was observed in 42 patients (37.50%) and severe steatosis (S3) in 41 patients (36.60%). Elevated AST levels (>2×upper limit of normal) were found in 54 patients (48.21%) and ALT in 57 patients (50.89%). High HBV DNA levels (>20,000 IU/mL) were present in 59 patients (52.67%). APRI score >1.5 showed a sensitivity of 85.71% and specificity of 79.55% (area under the curve [AUC]: 0.837), whereas FIB-4 score >3.25 had a sensitivity of 64.29% and specificity of 85.37% (AUC: 0.815). Both scores showed limited utility in detecting steatosis. Conclusion: FibroScan, APRI, and FIB-4 are effective non-invasive tools for assessing hepatic fibrosis in CHB patients. They offer viable alternatives to biopsy, especially in settings with limited resources.